2015
DOI: 10.1159/000439356
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy Management of Urolithiasis: Flexible Ureteroscopy versus Extracorporeal Shockwave Lithotripsy

Abstract: Objectives: To evaluate the efficacy of flexible ureterscopy (fURS) and extracorporal shockwave lithotripsy (SWL) in the treatment of urolithiasis, complemented by a subgroup analysis of lower pole calyx. Methods: Retrospective analysis of patients treated by fURS or SWL was performed by independent variables such as gender, age, nephrolith size, double-J stent (DJ stent) and stone localisation. Results: Out of 326 patients, 165 were treated by SWL and 161 by fURS. Complete stone removal was achieved by fURS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…A total of 2,265 patients were finally enrolled in our meta-analysis, of which 1,227 (54.17%) patients were enrolled in the f-URS group and the other 1,038 (45.83%) patients were enrolled in the SWL group. There were eight RCTs ( 18 , 22 , 23 , 26 29 , 31 ) and nine cohort studies ( 4 , 8 , 17 , 19 21 , 24 , 25 , 30 ) included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 2,265 patients were finally enrolled in our meta-analysis, of which 1,227 (54.17%) patients were enrolled in the f-URS group and the other 1,038 (45.83%) patients were enrolled in the SWL group. There were eight RCTs ( 18 , 22 , 23 , 26 29 , 31 ) and nine cohort studies ( 4 , 8 , 17 , 19 21 , 24 , 25 , 30 ) included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The management of LPS is one of the most interesting topics in urology, and discussions continue about the best treatment option. There are a limited number of comparative studies on the treatment of LPS with SWL and f-URS [ 6 - 8 ]. In this prospective study, we found a significantly higher stone-free rate following f-URS compared to SWL with similar complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the development of new ureteroscopes and progress of the manufacturing technology of ureteroscope-related accessory equipment, ureteroscopes are increasingly used in the diagnosis and treatment of upper urinary tract diseases, especially kidney stones (11). Holmium laser optic, basket extractor, nipper, and ureteroscope delivery sheath are tools for stone crush and removal.…”
Section: Discussionmentioning
confidence: 99%